Analysis of Psychological Status and Sleep Quality in Breast Cancer Patients - Endah Sari Purbaningsih; Muadi Muadi; Iin Indra Nuraeni (Eduvest - Journal of Universal Studies, 2022)
One of the health problems that many women experience is breast cancer. This diagnosis becomes a stressor that will greatly affect the patient's physical, psychological, spiritual and social condition. Another problem experienced by breast cancer patients is sleep disorders that can affect sleep quality. The purpose of this study was to determine the relationship between psychological status and sleep quality in breast cancer patients. The type or research design used is descriptive correlation with a cross sectional approach. The number of samples is 30 respondents, data collection using the standard DASS questionnaire for psychological status and PSQI for sleep quality, previously the patient was given informed consent. Data analysis using Spearman rank. The research was conducted at Waled Hospital, Cirebon. The results showed that there was a relationship between psychological status and sleep quality in breast cancer patients with p value = 0.004 < = 0.05. The correlation coefficient value of 0.509 means that the strength of the correlation is moderate and positive, meaning that the better the psychological status of the respondent, the higher the correlation. good sleep quality too. The conclusion of this study is that psychological status is positively correlated with sleep quality, the better the psychological status, the better the sleep quality of breast cancer patients.One of the health problems that many women experience is breast cancer. This diagnosis becomes a stressor that will greatly affect the patient's physical, psychological, spiritual and social condition. Another problem experienced by breast cancer patients is sleep disorders that can affect sleep quality. The purpose of this study was to determine the relationship between psychological status and sleep quality in breast cancer patients. The type or research design used is descriptive correlation with a cross sectional approach. The number of samples is 30 respondents, data collection using the standard DASS questionnaire for psychological status and PSQI for sleep quality, previously the patient was given informed consent. Data analysis using Spearman rank. The research was conducted at Waled Hospital, Cirebon. The results showed that there was a relationship between psychological status and sleep quality in breast cancer patients with p value = 0.004 < = 0.05. The correlation coefficient value of 0.509 means that the strength of the correlation is moderate and positive, meaning that the better the psychological status of the respondent, the higher the correlation. good sleep quality too. The conclusion of this study is that psychological status is positively correlated with sleep quality, the better the psychological status, the better the sleep quality of breast cancer patients.